A Distributed, Passivity-Based Control of Autonomous Mobile Sensors in an Underwater Acoustic Network. Issue 23 (2016) - Fabiani, F.; Fenucci, D.; Fabbri, T.; Caiti, A.
Abstract: This paper presents a cooperative and distributed control law for multiple Autonomous Underwater Vehicles (AUVs) executing a mission while meeting mutual communication constraints. Virtual couplings define interaction control forces between neighbouring vehicles. Moreover, the couplings are designed to enforce a desired vehicle-vehicle and vehicle-target spacing. The whole network is modelled in the passive, energy-based, port-Hamiltonian framework. Such framework allows to prove closed-loop stability using the whole system kinetic and virtual potential energy by constructing a suitable Lyapunov function. Furthermore, the robustness to communication delays is also demonstrated. Simulation results are given to illustrate the effectiveness of the proposed approach.